2013
DOI: 10.1159/000343917
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Molecular Characterization of a CSFV Strain Isolated from a CSF Outbreak in South China

Abstract: In the present study, the full-length nucleotide sequences of the CSFV-GZ-2009 strain of classical swine fever virus (CSFV) isolated from a hog pen in Guangdong province in China was determined. Results demonstrated that the genome of CSFV-GZ-2009 is 12,298 nucleotides (nt) in length, is composed of a 373-nt 5′-untranslated region (UTR), has an 11,697-nt open reading frame encoding a polyprotein of 3,898 amino acids, and has a 228-nt 3′-UTR. Genome comparison of the CSFV-GZ-2009 isolate (GenBank accession No. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Hence, C-vac is still a good choice for farmers. However, CSF was recently demonstrated to occur sporadically or endemically in many regions in China [ 16 , 41 , 42 , 43 , 44 ]. To completely control CSF, an elimination program is the only option.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, C-vac is still a good choice for farmers. However, CSF was recently demonstrated to occur sporadically or endemically in many regions in China [ 16 , 41 , 42 , 43 , 44 ]. To completely control CSF, an elimination program is the only option.…”
Section: Discussionmentioning
confidence: 99%
“…At present, CSF is still endemic in many Asian and Latin American countries, as well as in some countries from Eastern Europe [12,13]. Due to the huge harm of this disease, many countries have developed the eradication program against CSF [4]. What's more, our team has been working on the research of the pathogenesis of CSF, as well as the prevention and control of CSF [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Classical swine fever (CSF) is an economically important, highly contagious disease affecting pigs worldwide, characterized by high fever, hemorrhagic syndrome, and high mortality [1,2]. The causative agent of CSF is the classical swine fever virus (CSFV), an enveloped RNA virus that belongs to the Pestivirus within the family Flaviviridae [3,4]. Many molecular diagnostic methods for CSFV detection require sophisticated instruments, which is not convenient for clinical detection.…”
Section: Introductionmentioning
confidence: 99%
“…And identification of sub-genotypes 2.1c and 2.1d was based on the full-length E2 gene sequence [ 15 , 17 ]. Some labs reported that the whole genome sequence of CSFV could provide more reliable classification criterion [ 29 , 30 ]. In the present study, the phylogenetic tree was constructed based on the complete genomes.…”
Section: Discussionmentioning
confidence: 99%